Stress analysis of torispherical shell with radial nozzle - Ayob, Amran (The Institution Of Engineers, Malaysia, 2006)
The high stresses at intersections are caused by discontinuity shear stresses and moments which exist to maintain compatibility at the junction. The finite element method was used to determine the stress field at the intersection of a radial nozzle attached to a torispherical crown of a cylindrical vessel. The mechanical loads acting on the stru c t u re consisted of nozzle thrust, bending moment, torsion and internal pre s s u re. A comparison between predicted and measured readings gave acceptable results for internal pre s s u re loading but fair for other loadings. A computer program was written to calculate interaction between any two combining loads. The results, presented graphically, could be used to predict first yield for vessels of this configuration.